2022
DOI: 10.3390/educsci12030168
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Food Sustainability in Formal Education: A Teaching-Learning Sequence Contextualized in the Garden for Secondary School Students

Abstract: The purpose of this paper is to assess the impact of a garden-based teaching unit about “Food and Nutrition” on students’ knowledge and habits of sustainable healthy diets, and to compare it with that of a more traditional unit from a textbook. This communication is framed in a research project (EDUCYL2020-01 “Sembrando interés, cosechando competencia”, financed by the Consejería de Educación de la Junta de Castilla y León through the Dirección General de Innovación y Formación del Profesorado (ORDEN EDU/262/2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Internal consistency, assessed via composite reliability (>0.60), demonstrates solidity. Convergent validity, evaluated using AVE (>0.5), ensures that items within a construct measure the same concept (Erdfelder et al, 2015). Additionally, examining mean-variance extracted from each latent variable confirms convergent validity and assesses framework consistency (Fornell and Larcker, 1981).…”
Section: Assessment Of the Measurement Modelmentioning
confidence: 98%
See 1 more Smart Citation
“…Internal consistency, assessed via composite reliability (>0.60), demonstrates solidity. Convergent validity, evaluated using AVE (>0.5), ensures that items within a construct measure the same concept (Erdfelder et al, 2015). Additionally, examining mean-variance extracted from each latent variable confirms convergent validity and assesses framework consistency (Fornell and Larcker, 1981).…”
Section: Assessment Of the Measurement Modelmentioning
confidence: 98%
“…, 2022). In short, to leap over a view considering only health and nutrition from a sustainable approach (Eugenio-Gozalbo et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Out of 6,639 publications considered, nineteen were positively identified as peer-reviewed studies that quantitatively assessed the effectiveness of an educational interventions to encourage healthy eating through the lens of sustainability and climate change. Thirteen of these studies found that curricula highlighting the relationship between environmental sustainability and healthy, plant-based foods resulted in either increased knowledge about good nutrition, or increased consumption of plant-based foods (Antón-Peset et al, 2012;Bersamin et al, 2019;Brain et al, 2015;Cornelius et al, 2014;Costarelli et al, 2022;Eugenio-Gozalbo et al, 2022;Evans et al, 2012;Figueroa-Piña et al, 2021;Jones et al, 2012;Jones et al, 2017;Jones, 2020;Sellman & Bogner, 2013;Prescott et al, 2019). Six studies found no such positive relationship between the intervention and any predicted outcome.…”
Section: Personal Skills Needed For Successful Implementationmentioning
confidence: 99%